Neurodegeneration in Multiple Sclerosis: The Role of Nrf2-Dependent Pathways - Paloma P. Maldonado; Coram Guevara; Margrethe A. Olesen; Juan Andres Orellana; Rodrigo A. Quintanilla; Fernando C. Ortiz (Antioxidants, 2022)
Multiple sclerosis (MS) encompasses a chronic, irreversible, and predominantly immune-mediated disease of the central nervous system that leads to axonal degeneration, neuronal death, and several neurological symptoms. Although various immune therapies have reduced relapse rates and the severity of symptoms in relapsing-remitting MS, there is still no cure for this devastating disease. In this brief review, we discuss the role of mitochondria dysfunction in the progression of MS, focused on the possible role of Nrf2 signaling in orchestrating the impairment of critical cellular and molecular aspects such as reactive oxygen species (ROS) management, under neuroinflammation and neurodegeneration in MS. In this scenario, we propose a new potential downstream signaling of Nrf2 pathway, namely the opening of hemichannels and pannexons. These large-pore channels are known to modulate glial/neuronal function and ROS production as they are permeable to extracellular Ca2+ and release potentially harmful transmitters to the synaptic cleft. In this way, the Nrf2 dysfunction impairs not only the bioenergetics and metabolic properties of glial cells but also the proper antioxidant defense and energy supply that they provide to neurons.